Pelatihan Pembuatan Biogas dari Kotoran Ternak di Kecamatan Oebobo Kota Kupang - Rima Nindia Selan; Ben Vasco Tarigan; Kristomus Boimau; Muhamad Jafri (Jurnal Pengabdian Vokasi, 2021)
Oebobo Subdistrict is one of the six sub-districts in Kupang City. Based on data from the City of Sanitation and Landscaping Office of Kupang City, Oebobo District is a district with the largest volume of waste every day, which is 20.68 m3/ day. This is due to the densely populated area, which is also an office, school and hospital area, as well as a traditional market. Waste dumps that occur every day are almost entirely transported to the Final Disposal Site, located in Alak District. Waste management systems that are still based on the principle of Gathering - Transport - Dispose and are entirely dependent on the presence of the landfill, it is estimated that in the next 5-10 years waste management in Kupang City will experience problems with the end of the life of the landfill, while the location of the replacement landfill is increasingly difficult to obtain in connection with limited land and increasing community resistance to the existence of landfills. The waste problem can be overcome by proper waste management, so far in Oebobo District, the organic waste does not yet have proper management, therefore with the proposed program it is hoped that waste problems, especially organic waste, can be overcome. On the other hand by making biogas from organic waste, it can also help the community's economy. The gas produced can be used as a substitute for kerosene and LPG, which are increasingly scarce and expensive in the market.